Сausal analysis of environmental safety during production and use of pharmaceutical products - Вовк, О. О.; Бойченко, М. С. (Science-based technologies, 2017)
The paper first defines the purpose, subject, object, direction and objectives of the study the reasons and factors determining the condition and level of environmental safety during production and use of FP. Clarified the definition of «Farmaceutical products», updated the classification of waste. Performed causal analysis showed that the study of the life cycle of FP in the environment and determine their impact of waste on the variety of living organisms is a relevant applied science and social problem. To achieve this goal, we used the monographic method of establishing the relationship between causes, consequences and the state of environmental safety in the production and use of FP.